KEKUATAN HUKUM DARI HASIL MEDIASI DI PENGADILAN - Wijiatmawati, Ni Komang; Laksmi Danyathi, Ayu Putu (Kertha Semaya : Journal Ilmu Hukum, 2014)
Mediation is the one of the dispute resolution that do by a third party which is calledas mediator. The use of mediation have to done first when it conducted in the first trial ofcivil case and it aimed at resolving the civil case appropriate trilogy principles of justiceand reduce the cumulate of civil case in court. The result can be shape consent judgmentand amicable agreement. The purpose of this paper is knowing how far the power of lawresolved through mediation. This research used that normative methods that use primaryand secondary data sources.
Keywords: Mediation, Power of Law , Consent Judgment, Amicable Settlement